Interesting signs in facioscapulohumeral muscular dystrophy in a child - Sinha, Rahul; Pathak, Anuja (International Journal of Contemporary Pediatrics, 2025)
Facioscapulohumeral muscular dystrophy is the third most common muscular dystrophy in the world after Duchenne muscular dystrophy and myotonic dystrophy. The age of onset of FSHD varies from infancy to late adulthood. The prevalence ranges from 1:8000 to 20,000, with sixty percent of the disease population in Asian population. We report interesting signs in a genetically proven case of Facioscapulohumeral Muscular Dystrophy in a 9 years old child who had presented with facial muscle weakness, shoulder girdle weakness followed by hip girdle weakness. The clinician should be aware of this rare genetic condition especially when there is asymmetric weakness of facial and shoulder girdle muscles.